Um estudo didático das Cônicas: quadros registros e pontos de vista - Siqueira, Carlos Alberto Fernandes de (2016)
This research aims to construct a mathematical and didactic study of the conics in the scope of Geometry and Analytical Geometry from the outline of the methodology of the bibliographic research, in which we analyze documents that have already received an analytical treatment such as official documents of basic education, books, Dissertations, theses and articles related to the research topic. This analysis allowed the development of the research problem and the guiding question: How can the Frames, Viewpoints and Semiotic Representation Registers be articulated for the teaching of Conics in the basic cycle? In order to answer it we are based on the notions of Frames and Frames game, the Theory of Semiotic Representation Records and the notions of Viewpoints. In this sense, we verified that the articulation sought in the research question should consider the Tables of Geometry and Analytical Geometry, the View of the intersection between cone and straight circular plane, the View of the Geometric Place, the Point of View of Eccentricity And the Analytical Point of View, in addition to the Records of Semiotic Representation material, figural, figural dynamic, graphic and algebraic, as well as to seek treatments and conversions associated with these points of view. We point out for future investigations, that can carry out a study like this with a focus on higher education, considering the notions of Envolvente, Descriptive Geometry and Linear Algebra and studies that develop a didactic engineering with third year high school students and the organization of A teacher training, using this study as a basis to explore other relevant aspects that may complement this research